Smarter e-training system through applied cognitive task analysis: key insights - Idris, Aizal Yusrina (2025)
Abstract This poster presents the use of Applied Cognitive Task Analysis (ACTA) in the development of intelligent electronic training systems, illustrated through a case study of TaSPoD (E-Training System for Professional Development). ACTA is a practical, efficient methodology designed to capture expert cognitive processes, particularly in complex or high-stakes environments where observation alone is insufficient. It consists of four core techniques which are Task Diagram, Knowledge Audit, Simulation Interview and Cognitive Demand Table, which together enable the extraction of implicit expert knowledge and decision-making strategies. In this study, ACTA was applied within a Design-Based Research framework to guide the iterative design and refinement of TaSPoD, aimed at addressing limitations in existing professional development platforms such as poor usability, lack of adaptability and low learner engagement. The task diagram identified cognitively demanding areas such as system functionality and assessment design. The knowledge audit and simulation interviews revealed usability barriers, including unintuitive navigation, lack of real-time support and challenges in aligning assessments with learning outcomes. Insights from the Cognitive Demand Table were used to inform design improvements, focusing on reducing cognitive load and enhancing user experience. Findings demonstrate that ACTA not only captures expert thinking but also transforms it into actionable recommendations for improving system design, training effectiveness and learner support. By making expert cognition visible and usable, ACTA helps bridge the gap between expert and novice performance. This approach contributes significantly to the creation of more adaptive, intuitive and impactful e-training systems in education and beyond.